Excess Molar Enthalpies of Dibromomethane with Acetonitrile, Furan, Acetophenone and Tetrahydrofuran at T=313.15 K - Tripathi, Atri D. (Journal of Applied Solution Chemistry and Modeling, 2013)
Excess molar enthalpies have been determined for binary liquid mixtures of dibromomethane (CH2Br2) (DBM) with acetonitrile, furan, acetophenone and tetrahydrofuran at 313.15 K. The excess molar enthalpies are endothermic for the systems CH2Br2 + acetonitrile, and + furan whereas exothermic for the system CH2Br2 + acetophenone and + tetrahydrofuran over the whole composition range. The results were fitted with the Redlich- Kister equation by means of the least square method. These results indicate the existence of specific interactions between all these components.